Optimization of Subject Timetabling Based on Integer Linear Programming Using Microsoft Excel Solver - Ayu Larasati; Alma Aulia Hanifah; Sugiyanto Sugiyanto (Universitas Negeri Gorontalo, 2026)
Subject timetabling is an essential component of educational management because it involves allocating subjects, teachers, and instructional time while satisfying multiple scheduling constraints. Manual timetabling practices commonly used in schools often result in scheduling conflicts and require considerable effort when timetable revisions are necessary. Therefore, this study aims to develop and implement an Integer Linear Programming (ILP)-based subject timetabling model using Microsoft Excel Solver for MTs Nurul Ummah. The proposed model was formulated using binary decision variables, an objective function that minimizes scheduling penalties, and a set of constraints representing curriculum requirements, teacher availability, subject allocation, and instructional time. The model was implemented using Microsoft Excel Solver to generate a feasible timetable that satisfies the predefined scheduling constraints. The findings demonstrate that Microsoft Excel Solver provides a practical platform for implementing ILP-based subject timetabling in secondary schools without requiring specialized optimization software.